Intradialytic cardiac magnetic resonance imaging to assess cardiovascular responses in a short-term trial of hemodiafiltration and hemodialysis - Buchanan, Charlotte; Mohammed, Azharuddin; Cox, Eleanor; Köhler, Katrin; Canaud, Bernard; Taal, Maarten W.; Selby, Nicholas Michael; Francis, Susan T.; McIntyre, Christopher W. (American Society of Nephrology, 2016)
Hemodynamic stress during hemodialysis (HD) results in recurrent segmental ischemic injury (myocardial stunning) that drives cumulative cardiac damage. We performed a fully comprehensive study of the cardiovascular effect of dialysis sessions using intradialytic cardiac magnetic resonance imaging (MRI) to examine the comparative acute effects of standard HD versus hemodiafiltration (HDF) in stable patients. We randomly allocated 12 patients on HD (ages 32–72 years old) to either HD or HDF. Patients were stabilized on a modality for 2 weeks before undergoing serial cardiac MRI assessment during dialysis. Patients then crossed over to the other modality and were rescanned after 2 weeks. Cardiac MRI measurements included cardiac index, stroke volume index, global and regional contractile function (myocardial strain), coronary artery flow, andmyocardial perfusion. Patients had mean6SEMultrafiltration rates of 3.862.9 ml/kg per hour during HD and 4.462.5 ml/kg per hour during HDF (P=0.29), and both modalities provided a similar degree of cooling. All measures of systolic contractile function fell during HD and HDF, with partial recovery after dialysis. All patients experienced some degree of segmental left ventricular dysfunction, with severity proportional to ultrafiltration rate and BP reduction. Myocardial perfusion decreased significantly during HD and HDF. Treatment modality did not influence any of the cardiovascular responses to dialysis. In conclusion, in this randomized, crossover study, there was no significant difference in the cardiovascular response to HDF or HD with cooled dialysate as assessed with intradialytic MRI.